Recording process of judo training - Ferreira Pedrosa, G.; Teobaldo, B.; Januario, M.; Mota Soares, Y.; Fernandes Chaves Filho, A.; Riveiro Alves, G.; Szmuchrowski, L. A.; Sledziewski, D. (Archives of Budo Conference Proceedings, 2015)
Background & study aim: The judo training is highly complex and recording methods should help coaches to a better understanding of what is in fact been trained. The purpose of this study was recording the exercises performed by judo athletes during fourteen training sessions. Material and Methods: During fourteen days a digital camera video recorded the training of a judo team. The exercises were posteriorly analysed according to the magnitude, structure and dynamic through the time spent to perform each exercise. Results: 1422 minutes were recorded and the randori was the exercise more performed along the fourteen days training. The randori was always executed at the end of the training session with only two days exception. Specific exercises were more executed than general and special exercise. Conclusion: The recording process is an efficient method to analyze the magnitude, structure and dynamic of the exercises and can help to a better understanding on the adaptations caused by the training practice.